A Large Strain Computational Multi-Scale Model for the Dissipative Behaviour of Wood Cell-Wall - Saavedra-Flores, E (2011)
This paper investigates the non-linear irreversible behaviour of wood cell-walls by means of a finite element-based computational multi-scale approach. A finite strain three-scale model is proposed where the overall response of the cell-wall composite is obtained by the computational homogenisation of a Representative Volume Element (RVE) of cell-wall material, whose mechanical response prediction, in turn, involves the computational homogenisation of a cellulose core-RVE. Numerical material tests are conducted with the proposed model. The results are compared to published experimental data and demonstrate the predictive capability of the proposed model in capturing key features of cell-wall behaviour, such as viscous relaxation, recovery mechanism and hysteresis. The present results suggest a failure mechanism for the cell-wall under straining which is associated with the inelastic yielding of the amorphous portion of cellulose fibres. © 2010 Elsevier B.V. All rights reserved.